2008
DOI: 10.1021/bc800193p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Complexation Ability of a Novel Bis- (guanidinium)-tetrakis-(β-cyclodextrin) Dendrimeric Tetrapod as a Potential Gene Delivery (DNA and siRNA) System. Study of Cellular siRNA Transfection

Abstract: The facile synthesis of a novel bis-(guanidinium)-tetrakis-(beta-cyclodextrin) tetrapod, the first example of a new host family, was described, and the ability of the cyclodextrin CyD tetrapod to form molecular association with siRNA and DNA guest molecules was demonstrated. Affinity capillary electrophoresis was used to determine the binding constant with the evaluation of the shift in the electrophoretic mobility mu of injected siRNA when various CyD tetrapod concentrations were added to the run buffer. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…of -, -, and -configurations at molar ration of 1:1 (CyD:dendrimers) and found that CyD (G2) conjugates elicited approximately 100 times more luciferase gene transfer activity than non-covalent linked dendrimers and dendrimers (G2). 72 Followed by this experiment, Kihara et al 73 optimized many parameters to obtain stable, non-viral vectors with endosomal escaping ability, and his group found that -CyD with a degree of substitution (DS) of 2.4 was the best transfecting vector with a low cytotoxicity, i.e., the gene transfer ability of -CDE (G3, DS2) was superior to Transfast ™ and Lipofectin ™ . Menuel et al fabricated novel bis-(guanidinium)-tetrakis--CyDs tetrapod dendrimers as gene delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…of -, -, and -configurations at molar ration of 1:1 (CyD:dendrimers) and found that CyD (G2) conjugates elicited approximately 100 times more luciferase gene transfer activity than non-covalent linked dendrimers and dendrimers (G2). 72 Followed by this experiment, Kihara et al 73 optimized many parameters to obtain stable, non-viral vectors with endosomal escaping ability, and his group found that -CyD with a degree of substitution (DS) of 2.4 was the best transfecting vector with a low cytotoxicity, i.e., the gene transfer ability of -CDE (G3, DS2) was superior to Transfast ™ and Lipofectin ™ . Menuel et al fabricated novel bis-(guanidinium)-tetrakis--CyDs tetrapod dendrimers as gene delivery vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Guanidines have the extra advantage, being bidentate, of being able to form two hydrogen bonds with negatively charged groups e.g., carboxylates, phosphates or sulfates present on the carbohydrates associated with the cell membrane, and this advantage has been used in vectors e.g., R8, Arg 8 [11,12] to transport cargoes across cell membranes. These characteristics led to the design of many non-viral vectors for DNA and siRNA, varying from cationic lipids incorporating guanidine head-groups [13-15] e.g., AtuFECT [15], to cationic polymers [16,17] and dendrimers [18,19], to carbohydrate derivatives [19,20], and hydrogels of guanidinylated hyaluronic acid [21]. The use of guanidinium-containing lipid based carriers for gene delivery dates back to 1996 where Lehn et al synthesized two guanidinium cholesterol lipids: bis-guanidiniumspermidine-cholesterol (BGSC) and bis-guanidinium-trencholesterol (BGTC), each containing two guanidine groups, which were synthesized and evaluated for their DNA transfection efficiencies in eukaryotic cells (Figure 1) [22] where they were found to be efficient DNA transfecting agents.…”
Section: Introductionmentioning
confidence: 99%
“…DNA lipozomların içine enkapsüle olmaz fakat negatif yüklü olduğu için lipozomlara bağlanarak kompleksler oluşturur. Bu kompleks endozomlardan ve lipozomlardan salınır [49].…”
Section: Transfeksiyon Metotlarıunclassified